Autoimmune disease and interconnections with vitamin D - Fletcher, Jane; Bishop, Emma L; Harrison, Stephanie R; Swift, Amelia; Cooper, Sheldon C; Dimeloe, Sarah K; Raza, Karim; Hewison, Martin (Endocrine Connections, 2022)
Vitamin D has well documented effects on calcium homeostasis and bone metabolism but recent studies suggest a much broader role for this secosteroid in human health. Key components of the vitamin D system, notably the vitamin D receptor (VDR) and the vitamin D activating enzyme (1α-hydroxylase), are present in a wide array of tissues, notably macrophages, dendritic cells and T lymphocytes (T cells) from the immune system. Thus, serum 25-hydroxyvitamin D (25D) can be converted to hormonal 1,25-dihydroxyvitamin D (1,25D) within immune cells, and then interact with VDR and promote transcriptional and epigenomic responses in the same or neighbouring cells. These intracrine and paracrine effects of 1,25D have been shown to drive antibacterial or antiviral innate responses, as well as attenuating inflammatory T cell adaptive immunity. Beyond these mechanistic observations, association studies have reported correlation between low serum 25D levels and the risk and severity of human immune disorders including autoimmune diseases such as inflammatory bowel disease, multiple sclerosis, type 1 diabetes and rheumatoid arthritis. The proposed explanation for this is that decreased availability of 25D compromises immune cell synthesis of 1,25D leading to impaired innate immunity and over-exuberant inflammatory adaptive immunity. The aim of the current review is to explore the mechanistic basis for immunomodulatory effects of 25D and 1,25D in greater detail with specific emphasis on how vitamin D-deficiency (low serum levels of 25D) may lead to dysregulation of macrophage, dendritic cell and T cell function, and increase risk of inflammatory autoimmune disease.